2002
DOI: 10.1210/jcem.87.1.8185
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-9 Promotes the Growth, Development, and Survival of Human Ovarian Follicles in Organ Culture

Abstract: Growth differentiation factor-9 (GDF-9) is a growth factor and a member of the TGFbeta superfamily that is secreted by oocytes in growing ovarian follicles. In the current study we cultured human ovarian follicles within slices of ovarian cortical tissue in the presence and absence of recombinant rat GDF-9. Ovarian tissue was obtained by biopsy during cesarean section (31 women) or gynecological laparoscopy (3 women). The mean age (+/-SD) of the women who donated tissue was 32.8 +/- 5.0 yr (range, 19-41 yr). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(73 citation statements)
references
References 20 publications
5
61
0
7
Order By: Relevance
“…Despite encouraging results regarding functionality and developmental capacity of follicles under low-attachment conditions, the increasing atresia rate suggests that conditions for in vitro culture of frozen/thawed ovarian tissues still need to be optimized. Changes in the composition of the culture medium such as a supplementation with GDF-9, BMP15 and IGF-I which have been found to improve survival rate and promote follicular growth in culture, should be considered [20,23,27].…”
Section: Discussionmentioning
confidence: 99%
“…Despite encouraging results regarding functionality and developmental capacity of follicles under low-attachment conditions, the increasing atresia rate suggests that conditions for in vitro culture of frozen/thawed ovarian tissues still need to be optimized. Changes in the composition of the culture medium such as a supplementation with GDF-9, BMP15 and IGF-I which have been found to improve survival rate and promote follicular growth in culture, should be considered [20,23,27].…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the GDF-9 gene in mice blocked folliculogenesis at the primary stage, demonstrating the importance of this growth factor in early follicular development (29). Subsequent studies have shown that treatment with GDF-9 stimulates granulosa cell proliferation in rats (9), preantral follicle growth in humans (30) and goats (11) and cumulus cell expansion in humans (31) and results in a higher proportion of viable human follicles in organ culture, suggesting a possible role for GDF-9 in follicular survival (10). Moreover, the presence of GDF-9 in primary and later-stage goat follicles (32) suggests that GDF-9-mediated signaling events may be important for the development of preantral follicles in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Nilsson and Skinner (8) have shown that GDF-9 promotes the development of primary follicles in neonatal rat ovaries. Furthermore, recent studies have shown that GDF-9 stimulates the in vitro growth of preantral follicles and thecal cell differentiation in the rat (5,9) as well as primary and early secondary follicle formation in human ovarian slices in vitro (10). Recently, we have demonstrated that GDF-9 promotes in vitro follicular survival, growth and progression to the secondary follicle stage in goats, maintaining follicular ultrastructure (11).…”
Section: Introductionmentioning
confidence: 95%
“…Kuvvetle muhtemeldir ki overde lokal olarak üretilen baz› faktörlerin FSH ile etkileflimleri sonucu bu farkl›l›¤› yarat›yor olabilir. büyümekte olan sekonder folikül say›s›n› artt›rmaktad›r (40,(58)(59)(60) . GDF-9 geni olmayan farede folikül büyümesinin primer aflamada kalmas›da folikül büyümesinde bu büyüme faktörünün önemini göstermektedir (37,61,62) .…”
Section: Preantral Ve Antral Aflamalara Folikül Büyümesiunclassified